Higher education and SDG16 : peace, justice and strong institutions - Mendelson, Sarah Elizabeth (Emerald Publishing Limited, 2024)
Traditional approaches to teaching, researching, and advancing human rights need a refresh. The Sustainable Development Goals, the Leave No One Behind ethos, and the SDG16 agenda for peaceful, just, and inclusive communities offer a refreshed way to research and teach human rights and social justice in the twenty first century. Exploring how to ground an emerging paradigm shift and field build the next generation so that they approach human rights with a different lens and set of skills, this edited collection presents local case studies from cities and communities and considers their meaning for the rights movement globally. Emphasizing the need to reduce silos between domestic and international work, the chapters build on local "right to the city" activism and the global human rights cities movement to examine a local-global approach informed by city-level data, analyses, and practice. Higher Education and the Sustainable Development Goals is a series of 17 books that address each of the SDGs through the lens of higher education. Adopting a solutions-based approach, each book focuses on how higher education is advancing delivery of Agenda 2030. The series is edited by Wendy Purcell, Professor with Rutgers University and Academic Research Scholar with Harvard University; Emeritus Professor and University President Emerita.